Analisis Tingkat Kebugaran Jasmani Siswa Kelas VII SMPN 2 Brang Rea Berdasarkan Tes Kebugaran Jasmani Indonesia (TKJI) - Fathul Hidayat; Baiq Satrianingsih; Fadli Zainuddin (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to determine the physical fitness level of seventh-grade students at SMPN 2 Brang Rea based on the Indonesian Physical Fitness Test (Tes Kebugaran Jasmani Indonesia/TKJI), to identify the distribution of students' physical fitness categories, and to determine the most dominant and the lowest physical fitness components. This research employed a quantitative approach with a descriptive research design. The participants consisted of 77 seventh-grade students of SMPN 2 Brang Rea. The instrument used in this study was the Indonesian Physical Fitness Test (TKJI) for the 13–15 years age group, which includes five test items: a 50-meter sprint, bent-arm hang/pull-up, 60-second sit-up, vertical jump, and an 800-meter run for female students or a 1000-meter run for male students. Data were analyzed using descriptive statistical techniques in the form of frequencies, percentages, and categorization based on TKJI norms. The results of the study revealed that the overall physical fitness level of seventh-grade students at SMPN 2 Brang Rea was in the good to moderate category. The distribution of physical fitness levels indicated that the good category was the most dominant among students. The highest achievement was found in the arm muscle strength and endurance component, measured through the bent-arm hang or pull-up test, while the lowest achievement was observed in the cardiorespiratory endurance component, measured through the 800-meter and 1000-meter run tests. These findings indicate that students generally possess an adequate level of physical fitness; however, improvements are still needed, particularly in cardiovascular endurance, through regular physical activities and structured exercise programs. Keywords: Physical Fitness, Junior High School Students, Physical Education, TKJI, Indonesian Physical Fitness Test